Natural products for the treatment of ulcerative colitis: focus on the JAK/STAT pathway - Long, Dan; Mao, Chenhan; Zhang, Wei; Zhu, Ying; Xu, Yin (Frontiers in Immunology, 2025)
Ulcerative colitis (UC) is an autoimmune disease with an incompletely understood pathogenesis. The Janus kinase (JAK)/signal transducer and activator of transcription (STAT) signaling pathway plays a key role in immune response and inflammation. More and more studies demonstrated that JAK/STAT signaling pathway is associated with the pathogenesis of UC. The JAK/STAT pathway affects UC in multiple ways by regulating intestinal inflammatory response, affecting intestinal mucosal barrier, modulating T cell homeostasis, and regulating macrophages. Encouragingly, natural products are promising candidates for the treatment of UC. Natural products have the advantage of being multi-targeted and rich in therapeutic modalities. This review summarized the research progress of JAK/STAT pathway-mediated UC. Furthermore, the latest studies on natural products targeting the JAK/STAT pathway for the treatment of UC were systematically summarized, including active ingredients such as arbutin, aloe polysaccharide, berberine, matrine, curcumin, Ginsenoside Rh2, and so on. The aim of this paper is to provide new ideas for drug development to regulate JAK/STAT signaling for treating UC.